Sejarah dan Peran Muhammadiyah untuk Kemajuan Indonesia - Aisyah Khoirunni’mah Al Mufarriju (Jurnal Budi Pekerti Agama Islam, 2024)
The presence of Muhammadiyah in Indonesian history has been an important part of the journey of social progress, education and social welfare. This article discusses the significant role of Muhammadiyah in encouraging Indonesia's development from time to time. This research uses a historical approach to analyze Muhammadiyah's role in fighting for independence, building educational infrastructure, and promoting the values ​​of social justice and prosperity. Key words such as "Muhammadiyah", "history", "role", and "progress" are the main focus in this discussion. The findings show that Muhammadiyah is not only a religious movement, but also a social force that has played a role in changing the face of Indonesia. Through inclusive education, community empowerment, and justice efforts, Muhammadiyah continues to contribute to advancing this nation. The implications of this research provide deep insight into how religious organizations can become agents of positive change in building a more civilized and advanced society.